Déficit hídrico em milho: caracterização fisiológica e inoculação com azospirillum brasilense - Pedersen, Ana Cláudia (2013)
The events that occur in the growth and development of plants are vital to obtain great yield, however require an adequate supply of water. Because of these aspects, water is the most limiting factor to obtain high yield. The corn crop is widespread in Brazil, and has high water consumption. There are plenty bacterias, called diazotrophic, that besides the nitrogen fixation also promote root growth, allowing the plant to explore a larger volume of soil. This work was conducted in order to characterize the physiological aspects of the corn plants in water deficit conditions and evaluate the inoculation with Azospirillum brasilense in corn under conditions of water restriction. The experiment was conducted in a greenhouse using seeds with and without inoculation with the bacteria, totaling 160 pots in randomized blocks. The pots were subjected to four different pot capacities and assessed between 10 and 16 hours, with intervals of two hours, with five replicates. The assessments, done in the fifth leaf, were stomatal conductance, leaf temperature, chlorophyll content and chlorophyll fluorescence. The vegetative growth evaluation did not use the treatment hours, measuring height, stem diameter, total and unit leaf area, dry mass of roots, stems and leaves. Inoculation with Azospirillum brasilense (CMS CMS 7 and 712) does not affect the vegetative growth and physiological behavior of the hybrid corn Status. Water deficit alters the physiological behavior of corn hybrid Status